Budgeting in Estonia - Kraan, Dirk-Jan (OECD Publishing, 2008)
Since independence, Estonia has been at the forefront of institutional reform in the area of financial management. Budget formulation is divided into two distinct stages: strategic planning and preparation of the annual budget that is submitted to Parliament. This article describes key characteristics of budgeting in Estonia, including the development of the State Budget Strategy, the parliamentary process, the organisation of budget execution, and systems for accounting and auditing